Towards Long‐Term Photostability of Nickel Hydroxide/BiVO4 Photoanodes for Oxygen Evolution Catalysts via In Situ Catalyst Tuning. (12th February 2020) - Gao, Rui‐Ting; He, Dan; Wu, Lijun; Hu, Kan; Liu, Xianhu; Su, Yiguo; Wang, Lei
Abstract: Increasing long‐term photostability of BiVO4 photoelectrode is an important issue for solar water splitting. The NiOOH oxygen evolution catalyst (OEC) has fast water oxidation kinetics compared to the FeOOH OEC. However, it generally shows a lower photoresponse and poor stability because of the more substantial interface recombination at the NiOOH/BiVO4 junction. Herein, we utilize a plasma etching approach to reduce both interface/surface recombination at NiOOH/BiVO4 and NiOOH/electrolyte junctions. Further, adding Fe 2+ into the borate buffer electrolyte alleviates the active but unstable character of etched‐NiOOH/BiVO4, leading to an outstanding oxygen evolution over 200 h. The improved charge transfer and photostability can be attributed to the active defects and a mixture of NiOOH/NiO/Ni in OEC induced by plasma etching. Metallic Ni acts as the ion source for the in situ generation of the NiFe OEC over long‐term durability. Abstract : Ätzend : Einfaches Plasmaätzen wurde verwendet, um die Grenzflächen/Oberflächen‐Rekombination an NiOOH/BiVO4 ‐ und NiOOH/Elektrolyt‐Kontakten für die katalytische photoelektrochemische (PEC) Sauerstoffentwicklung zurückzudrängen. Die Zugabe von Fe 2+ in den Boratpufferelektrolyten milderte den aktiven, aber instabilen Charakter des geätzten NiOOH/BiVO4, was zu einer hervorragenden Photostabilität über 200 h führte.